(R)‐2, 3‐Cyclohexylideneglyceraldehyde, a Chiral Pool Synthon for the Synthesis of 2‐Azido‐1, 3‐diols. Issue 6 (June 2015) - Rouf, Abdul; Aga, Mushtaq A.; Kumar, Brijesh; Taneja, Subhash C.
Abstract A new approach was proposed for the synthesis of 2‐azido‐1, 3‐diols from easily available and inexpensive chiral pool synthon (R)‐2, 3‐O‐cyclohexylidene‐D‐glyceraldehyde, through Mitsunobu azidation of 1, 2‐diols. Both C(2) and C(1) azides in variable ratios were obtained in alkyl substituted diols with C(2) as the major one.